Board gender diversity and firms' internationalization speed: the role of female directors' characteristics. Issue 1 (22nd November 2021) - Ren, Ge; Zeng, Ping
Abstract : Purpose: Drawing on the gender self-schema theory, upper echelons theory and the literature on international business, this study aims to examine the impact of board gender diversity on firms' internationalization speed. Design/methodology/approach: In this study, secondary data of 886 listed Chinese manufacturing firms from 2009 to 2018 are studied using the ordinary least squares regression model as the baseline method, an instrumental variable method is adopted for endogeneity control and both fixed and random effect models are adopted for the robustness test. Findings: Board gender diversity reduces firms' internationalization speed, and the negative effect between board gender diversity and internationalization speed is stronger when the average age of female directors is older and weaker when female directors have international experience or financial background. Practical implications: First, Chinese firms need to increase or decrease board gender diversity to match the board to firms' internationalization strategy. Increasing board gender diversity may be a more appropriate choice for firms that are expanding rapidly internationally, and vice versa. Second, when introducing female directors to international firms, it is essential to address other characteristics of these directors beyond their gender. Originality/value: First, the authors contribute to the literature on board gender diversity using Chinese manufacturing firms as our research sample, which provides new insights into the economic consequences of increasing the number of female directors. Second, this research contributes to the literature on firms' internationalization speed. Third, the authors capture in more detail the economic consequences of increasing board gender diversity in the context of China.